Numerical Simulation and Experimental Investigation of Quantum Dash Lasers at Elevated Temperatures: Design and Operation of Monolithic InAs/InP Quantum Dash Ridge Laser Diodes Operating in the C-Band - Schaefer, Sebastian (Université d'Ottawa | University of Ottawa, 2024)
The ever increasing data streams transmitted via optical networks, combined with a growing interest in reducing the energy consumption of these same networks, have made it clear that a new generation of light sources is needed for the networks of the future. In this work, we examine one candidate device, a mode-locked ridge waveguide quantum dash laser. Quantum dash and dot gain media both exhibit spontaneous mode-locking, reduced sensitivity of their performance to temperature, and lower threshold current densities. Dashes additionally offer higher peak gain and broader gain bandwidths, but show higher phase noise than dots. We develop a quantum dash laser model in a commercial laser simulation package, Crosslight PICS3D, that predicts several device performance characteristics, including threshold current density and slope efficiency. The model is calibrated to experimental results at temperatures of up to 70°C. Using the numerical model, we identify the crucial role the wetting layer plays in the overall device behaviour. Its ability to capture and trap carriers accounts for a significant portion of the non-radiative recombination occurring in these devices and is a major driver in the roll-off observed for higher current densities and temperatures. The model is then used to test a variety of design considerations that would offer potential pathways towards a higher performing device, creating a short list of considerations that are to be examined experimentally. Three proposed designs were grown and fabricated. The designs studied varied the number of quantum dash layers, increased the quantum dash layer spacing within the separate confinement heterostructure, and added an unipolar barrier to prevent electron escape into the p-cladding. We find that the addition of a 100 nm InAlAs barrier at the interface between the separate confinement heterostructure and the p-cladding increases the wall plug efficiency by up to 20% at elevated temperatures without altering the lasing spectrum bandwidth.
Keywords: laser; numerical simulation; semiconductor; quantum dash; quantum dot; temperature-dependence; telecommunications; fiber-optical networks